Regional innovation systems: Systematic literature review and recommendations for future research - Ricardo M. Pino (Taylor & Francis Group, 2018)
The theoretical and practical development of the innovation concept is relevant in academic and economic arenas, and the regional systemic perspective of innovation is gaining ground as a solid approach in understanding this phenomenon and its components. This article analyzes the content and evolution of academic research on Regional Innovation Systems (RIS) from 1997 to September 2017. A rigorous search of articles about RISs published in top journals within the ISI Web of Knowledge was conducted. The selection of journals was based on their scores on the Scimago Journal & Country Rank. Descriptive and content analyses of the articles were performed and general statistics are presented. This study summarizes how literature has defined RIS, what are the components of RIS according to published papers, and how to measure performance of RIS. The article includes the identification of knowledge gaps in the field and some recommendations for future research.